PENGARUH MEDIA TANAM YANG BERBEDA TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS TANAMAN SAWI HIJAU (Brassica juncea L.) SECARA HIDROPONIK NFT - Gafar, Afan; Rusmana, Rusmana; Sodiq, Abdul Hasyim; Rohmawati, Imas (Agros Journal of Agriculture Science, 2023)
The use of a hydroponic cultivation system is an alternative to increase the productivity of vegetable plants whose cycles are quite short. It is hoped that the use of the NFT hydroponic technique can increase the productivity of mustard plants. This study aims to determine the effect of different planting media and several varieties on the growth and yield of mustard greens (Brassica juncea L.) using NFT hydroponics. This research was an experimental type that was prepared using a Randomized Block Design (RAK) with 2 factors, namely the use of planting media and varieties with repetition 3 times, and there were 9 treatment combinations. Data were analyzed using ANOVA and tested using the Duncan Multiple Range Test (DMRT) at the 5% level. The results of the research showed that the plant height parameters for the combination of treatment m3v1 using Rockwool planting media and the Tosakan variety for plants were 7 DAP (8.47 cm) and 14 DAP (21.58 cm), as well as the combination treatment m1v1 for using charcoal husk and the Tosakan variety for plants at 28 DAP ( 33.97 cm), leaf number parameters in the combination treatment m1v2 using husk charcoal and the Tosakan variety for 28 HST plants (33.97 cm). Parameters for the number of plant leaves with the m3v3 treatment combination, namely the use of Rockwool planting media and the Kumala variety, 21 HST (11.50 pieces) and 28 HST (24.50 pieces) plants. Key-words: Planting media, NFT, Mustard Greens.                INTISARI                  Penggunaan sistem budidaya hidroponik menjadi salah satu alternatif untuk meningkatkan produktivitas tanaman sayuran yang siklusnya cukup pendek. Penggunaan teknik hidroponik NFT diharapkan dapat meningkatkan produktivitas tanaman sawi. Penelitian ini bertujuan untuk mengetahui pengaruh media tanam yang berbeda dan beberapa varietas terhadap pertumbuhan dan hasil tanaman sawi hijau (Brassica juncea L.) dengan menggunakan hidroponik NFT. Penelitian ini berjenis eksperimen yang disusun dengan menggunakan Rancangan Acak Kelompok (RAK) 2 faktor, yaitu penggunaan media tanam dan varietas dengan pengulangan sebanyak 3 kali, dan terdapat 9 kombinasi perlakuan. Data dianalisis dengan ANOVA dan diuji dengan menggunakan Duncan Multiple Range Test (DMRT) pada taraf 5%. Hasil penelitian menunjukkan bahwa parameter tinggi tanaman kombinasi perlakuan m3v1 penggunaan media tanam rockwool dan varietas Tosakan tanaman 7 HST (8,47 cm) dan 14 HST (21,58 cm), serta kombinasi perlakuan m1v1 penggunaan arang sekam dan varietas Tosakan tanaman 28 HST (33,97 cm), parameter jumlah daun pada kombinasi perlakuan m1v2 penggunaan arang sekam dan varietas Tosakan tanaman 28 HST (33,97 cm). Parameter jumlah daun tanaman dengan kombinasi perlakuan m3v3 yaitu penggunaan media tanam rockwool dan varietas Kumala tanaman 21 HST (11,50 helai) dan 28 HST (24,50 helai). Kata kunci: Media tanam, NFT, Sawi hijau